ETIKOLEGAL HAK MENOLAK PERAWATAN PADA MASA PANDEMI: PERTENTANGAN HAK INDIVIDU DAN MASYARAKAT - Hari Pudjo Nugroho (Jurnal MHKI, 2021)
During the Covid-19 pandemic, where transmission is effortless to transmit between humans, the patient's right to accept or refuse part or all of the treatment or treatment for himself is abolished because it is to protect the rights of others and the community so as not to become infected by these patients. The patient's right to participate is excluded if the patient is suffering from a disease categorized as fast-spreading. The patient is in a condition of incapability to make decisions. The patient's participatory right to refuse or accept part or all of the treatment to be given to him or her forms the basis of other rights provided for by law. The patient's participatory right does not eliminate the patient's responsibility not to transmit the disease to others. The burden of this patient has been regulated in the existing laws and regulations, even up to maximum remedial punishment. Statute approach and conceptual-eclectic (conceptual approach) to Law Number 36 of 2009 concerning Health regarding the norms of preventing the transmission of disease outbreaks.  To further provide a critical note for normalization and implementation of the law, which is expected to provide justice for the legal interests of individuals and society.